PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE KARTU ARISAN UNTUK MENINGKATKAN KERJA SAMA SISWA KELAS V SEKOLAH DASAR - Dea Mirnanda; Dwi Viora; Muhammad Syahrul Rizal; Melvi Lesmana Alim; Mohd. Fauziddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the author's concern regarding the lack of student collaboration in Indonesian language learning. Indonesian language learning needs to emphasize the attitude of cooperation among individuals in a group to complete tasks, share information and knowledge, and work together in a group to complement each other in achieving common goals. The purpose of this study is to improve student collaboration in the Indonesian language subject for fifth-grade students at State Elementary School 003 Pulau Jambu, Kuok District. This research was conducted in the even semester of the 2024/2025 academic year at State Elementary School 003 Pulau Jambu, Kuok District. The research method used is classroom action research (CAR). The subjects of this study are the fifth-grade students of State Elementary School 003 Pulau Jambu, Kuok District, for the 2024/2025 academic year. Data collection was conducted using observation sheets as instruments. Data analysis utilized both qualitative and quantitative tests. The results of this study indicate that the application of the cooperative model type lottery cards can improve collaboration among fifth-grade students at State Elementary School 003 Pulau Jambu, Kuok District. The improvement can be seen from the number of students collaborating in cycle I, which consisted of 15 students with a percentage of 65.21%, and the number of students who did not collaborate, which amounted to 8 students with a percentage of 34.78%. In cycle II, the number of students collaborating increased to 21 students with a percentage of 91.30%, while the number of students who did not collaborate decreased to 2 students with a percentage of 8.69%. Since the number of students who did not collaborate decreased from cycle I to cycle II, this research is considered successful.